Muslim Andalusia: new insights into linguistic and literary exchanges between the East and the West - Bahjat, Munjid Mustafa; Ramdane, Tahraoui; Preece, Abdul Shakour Duncan (IIUM press, 2017)
This paper offers a new perspective on the cultural relations between Arab Muslims of the East and Christians of the West, in medieval Iberia, (known as al-Andalus by the Muslims) from 711 to 1031 C.E; identifying the benefits that emerged from such relations. Evidence was extracted from primary historical sources, including the travel writings of Ibn Hayyan and Ibn Jubayr, along with other western sources and documents born out of the academic exchange of ideas and literature between Muslim Spain and the European states of the time. Furthermore, the discourse within the study draws upon manuscripts and studies that transcend the stereotypical images of the victors and the defeated. The main thesis of the study argues that universal values and mutual respect between Muslim and non-Muslim communities of medieval Spain, were in fact the norm and not the exception. Moreover, it shows that literature, in all its forms, had a significant impact on the development and maintenance of harmonious, peaceful relations between Muslims and non-Muslims (mainly Christian). The paper highlights the synthesis between the Arabic and Spanish languages, between Arabic and European poetry and between Arab and European tales and stories. The findings of the study contest the idea of a clash of civilizations and instead, demonstrate how in medieval Spain, people of different creeds and cultures communicated and interacted successfully, in spite of their differences.